Own Risk and Solvency Assessment within the Solvency II Framework and its interplay with the quantitative solvency capital requirements - Helmut Gründl; Jens Gal (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
Pursuant to art. 45 of the Solvency II Framework Directive, all insurance undertakings will be obliged to conduct an "Own Risk and Solvency Assessment" (ORSA). ORSA's relevance is not limited only to the second pillar of Solvency II, where mainly qualitative requirements are to be found. ORSA rather exhibits strong interlinks with the first pillar and its quantitative requirements and may also serve as a trigger for transparency duties which form Solvency II's third pillar. ORSA may thus be described in some respects as the glue that binds together all three pillars of Solvency II. ORSA is one of the most obvious examples of the supervisory shift from a rules-based to a principles-based approach. As such, ORSA has hitherto been only very roughly defined. Since it is for the undertaking to determine its own specific risk profile and to evaluate whether this risk profile deviates significantly from the assumptions underlying the standard formula, it seems only natural that the supervisor must specify in greater detail what these underlying assumptions are. The most practicable way to do so would be for EIOPA to establish a "standard insurer", which implies a translation of the assumptions concerning the underlying probability distributions into directly observable characteristics. The creation of the standard insurer would be an important step towards relaxing the insurers' fear of what ORSA might bring about.
urn:nbn:de:hebis:30:3-294790
Keywords: 330; Insurance; Own Risk and Solvency Assessmen; Solvency II